Cellular Response to Ciprofloxacin in Low-Level Quinolone-Resistant Escherichia coli - Machuca, Jesús; Recacha, Esther; Briales, Alejandra; Díaz-de-Alba, Paula; Blazquez, Jesús; Pascual, Álvaro; Rodríguez-Martínez, José-Manuel (Frontiers in Microbiology, 2017)
Bactericidal activity of quinolones has been related to a combination of DNA fragmentation, reactive oxygen species (ROS) production and programmed cell death (PCD) systems. The underlying molecular systems responsible for reducing bactericidal effect during antimicrobial therapy in low-level quinolone resistance (LLQR) phenotypes need to be clarified. To do this and also define possible new antimicrobial targets, the transcriptome profile of isogenic Escherichia coli harboring quinolone resistance mechanisms in the presence of a clinical relevant concentration of ciprofloxacin was evaluated. A marked differential response to ciprofloxacin of either up- or downregulation was observed in LLQR strains. Multiple genes implicated in ROS modulation (related to the TCA cycle, aerobic respiration and detoxification systems) were upregulated (sdhC up to 63.5-fold) in mutants with LLQR. SOS system components were downregulated (recA up to 30.7-fold). yihE, a protective kinase coding for PCD, was also upregulated (up to 5.2-fold). SdhC inhibition sensitized LLQR phenotypes (up to Log=2.3 after 24 hours). At clinically relevant concentrations of ciprofloxacin, gene expression patterns in critical systems to bacterial survival and mutant development were significantly modified in LLQR phenotypes. Chemical inhibition of SdhC (succinate dehydrogenase) validated modulation of ROS as an interesting target for bacterial sensitization.